Analisis Cemaran Eschericia coli pada Minuman Cendol yang Dijual di Komplek MMTC dan Sekitarnya - Toberni S Situmorang; Rahmiati Rahmiati; Helen Anjelina Simanjuntak (Mahesa Research Center, 2023)
Eschericia coli bacteria are fecal coliform bacteria that belong to the Enterobacteriaceae group. This bacterium is an indicator of water quality to test for fecal contamination in a water sample. Cendol is a drink that has many fans because of its sweet and savory taste. The high consumption of cendol in the community is the basis for this drink to maintain its quality. One of the qualities that must be considered is the microbiological quality. The research was carried out in a quantitative descriptive manner and the research data will be displayed in the form of data tabulations. There were 3 samples of cendol tested namely TS1, TS2 and TS3. There were 3 stages in conducting the research, namely sample preparation, counting of total bacteria and testing of Eschericia coli bacteria on selective eosin methylene blue agar (EMBA) media. The results of the analysis showed that the total number of bacteria in the cendol samples tested on samples TS1, TS2 and TS3 were 1.2 x 104 colonies respectively; 4.8 x 104 colonies and 6.6 x 104 colonies. The results of the analysis of E. coli bacteria in the three samples showed that the three samples showed the growth of E. coli bacteria in the test medium. Colonies of E. coli bacteria on EMBA media are marked by the growth of metallic green colonies